Changes in the Element Composition of Globoids from Cucurbita Maxima and Cucurbita Andreana Cotyledons During Early Seedling Growth - Beecroft, Penny (My University, 1994)
The cells of 𝘊𝘶𝘤𝘶𝘳𝘣𝘪𝘵𝘢 embryos contain may protein bodies surrounded by smaller lipid vesicles. Within the protein bodies are discrete spherical bodies called globoids. Globoids are made up of phytin, and are an important store of 𝘮𝘺𝘰-inositol, phosphorus, and cations including K, Mg, Ca, Mn, Fe and Zn. During early seedling growth, the protein bodies fuse together to form aqueous vacuoles, and the globoids are degraded, their mineral nutrient stores used by the growing seedling. The changes in the element composition of globoids during early seedling growth were examined in this study and the influence of light and mineral nutrient conditions on the changes were examined. Energy dispersive X-ray analysis was used to determine the element composition of globoids from the cotyledons of 𝘊. 𝘮𝘢𝘹𝘪𝘮𝘢 and 𝘊. 𝘢𝘯𝘥𝘳𝘦𝘢𝘯𝘢 seeds and seedlings at various stages of growth. The stages selected ranged from the mature, dry seed, to an established seedling with an elongated hypocotyl and expanded cotyledons. To investigate the influence of light and mineral nutrient conditions, seedlings were grown under four different sets of growth conditions: in the dark, with deionized water; in the dark, with Hoaglands solution; in the light, with deionized water; in the light, with Hoaglands solution. During early seedling growth, the element composition of globoids changed. In both species, regardless of growth conditions, the same general trend was observed for each element: P remained relatively constant, K decreased markedly and Mg, Ca, Mn, Fe, and Zn generally increased. As the protein bodies fused and became more aqueous, it appeared that K ions came off the phytate molecule and were replaced by di-and trivalent cations with a higher affinity for phytic acid. There were species-to-species differences in globoid composition changes which could be attributed, at least in part, to differences in the Ca content of the mature, dry embryos. In 𝘊. 𝘢𝘯𝘥𝘳𝘦𝘢𝘯𝘢, which had a higher initial Ca content, there was a large increase in the Ca content of the globoids during seedling growth and no significant increase in Mn. In 𝘊. 𝘮𝘢𝘹𝘪𝘮𝘢 globoids there was only a slight increase in Ca, but there was a much larger increase in Fe, Zn and Mn than occurred in 𝘊. 𝘢𝘯𝘥𝘳𝘦𝘢𝘯𝘢. Light and dark grown seedlings exhibited distinctly different morphological features, but light conditions alone did not have a significant influence on the changes in globoid composition. In combination with mineral nutrients in the later stages of growth, the presence of light resulted in a more rapid degradation of globoids. Mineral nutrient conditions had some effect on globoid composition, affecting mostly elements which were present in large amounts. The effect of mineral nutrient conditions, and its interactions with light conditions may have been mediated through changes in the mobilization of mineral nutrients out of the cotyledons during seedling growth. There were very large (5 -7μm in diameter) globoid-like particles present in some later stage cotyledon samples of both species. There was no apparent pattern to which samples they were found in. These particles had elemental compositions which were consistent with them being composed of phytin. Such large particles had not previously been found in cucurbit tissues.
Changes in Globoid Composition During Early Seedling Growth
Keywords: globoids; Cucrubita; seed; growth; element